Um olhar autoetnográfico sobre a branquitude nos Núcleos de Estudos Afro-brasileiros e Indígenas (NEABI) de um Instituto Federal de Educação, Ciência e Tecnologia - Holanda, Lara Söldon Braga (2023)
This work aimed to analyze the representations of racism and whiteness that permeate the activities of the Afro-Brazilian and Indigenous Studies Centers (NEABIs), of the Federal Institute of Education, Science and Technology of Ceará (IFCE). The research was structured using a qualitative methodological approach, from an autoethnographic perspective. This approach enabled critical observation of the researched phenomenon, involving different perspectives and perspectives, both from the research participants and the researcher herself, based on an ethical relationship of reciprocity, dialogicity, respect for differences and selfreflection. Data collection took place in three ways: I. Bibliographic and documentary research, in order to characterize the performance of NEABIs at IFCE; II. Sharing a questionnaire with twelve coordinators of the aforementioned groups, and III. Semi-structured interviews with six members of the same nucleus. As main results, it was observed that the racial self-perceptions of the research subjects interfere in the way they perceive and reflect on ethnic-racial issues. Furthermore, it was possible to infer that NEABI participants, both coordinators and members, conceive whiteness as a place of privilege, in a society structured and hierarchized by racism, in which institutions represent vital tools for maintaining and reproducing this structure that privileges few and excludes many. Furthermore, it was found that, although establishing itself as a basic theme for understanding and confronting racial inequalities and racism, the discussion about whiteness is still incipient in the context of IFCE's NEABIS, although these are recognized almost unanimously by the subjects of research, as legitimate spaces for discussing this topic.